2014
DOI: 10.11114/jets.v2i4.496
|View full text |Cite
|
Sign up to set email alerts
|

"The Joy of Reading" - An Intervention Program to Increase Reading Motivation for Pupils with Learning Disabilities

Abstract: This study aimed to examine the effect of an intensive reading intervention on reading motivation. The intervention program, ("Joy of Reading"), was implemented in six 2 nd grade special education classes for pupils with learning disabilities, compared to a control group (n=108 pupils in total).The intervention program was created based on learning principles that were proven effective among children with learning disabilities, included intensive exposure to daily structured reading activities, encouraging pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Through the analysis of teachers' interview data, it can be concluded that in addition to helping students with CV + CVC word reading skills, students also responded positively by helping their peers pronounce the words and also showed no boredom during the learning session using the LSR interactive application. This is in line with the study findings of [7] in 'The Joy of Reading "-An Intervention Program to Increase Reading Motivation for Pupils with Learning Disabilities which showed that using innovative tool had a significant effect in assisting students with cognitive problems in mastering their reading skills. In addition, active learning activities using this innovative tool in 'The Joy of Reading' created a positive learning experience involving mastery of language literacy through a variety of interesting learning activities such as reading reports, role play and sharing of ideas based on reading materials read.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Through the analysis of teachers' interview data, it can be concluded that in addition to helping students with CV + CVC word reading skills, students also responded positively by helping their peers pronounce the words and also showed no boredom during the learning session using the LSR interactive application. This is in line with the study findings of [7] in 'The Joy of Reading "-An Intervention Program to Increase Reading Motivation for Pupils with Learning Disabilities which showed that using innovative tool had a significant effect in assisting students with cognitive problems in mastering their reading skills. In addition, active learning activities using this innovative tool in 'The Joy of Reading' created a positive learning experience involving mastery of language literacy through a variety of interesting learning activities such as reading reports, role play and sharing of ideas based on reading materials read.…”
Section: Discussionsupporting
confidence: 89%
“…Further, [7] in his study stated that the enjoyment of reading in the classroom of learning disabilities will increase if there are guidance and teaching aids that meet the needs of students. Teachers act as a mediator to show that reading is an exciting and enjoyable learning activity.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies explored the problem of children's low or declining motivation for reading by suggesting intervention programs at different grade levels [20]- [22]. The use of AR applications in an educational environment for enhancing motivation is a relatively recent development [23].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier contributions explored the problem of low or declining motivation for reading by suggesting intervention programs that did not necessarily use technology [20], [21] and interventions that involved e-reading on screens [22] and AR textbooks [23] that indicated that technologically supported interventions have the potential to increase students' reading motivation. Previous studies focused on the impact of AR tools in different levels of formal education and different application domains.…”
Section: Related Workmentioning
confidence: 99%
“…Additional components, such as systematic exposure to schema story discourse, linguistic enrichment and social values, were added through various activities. The intervention program helped students with LD adopt reading habits as an enjoyable way to spend time (Tovli, 2014).…”
mentioning
confidence: 99%